Predicting Performance Level of Reinforced Concrete Structures Subject to Corrosion as a Function of Time - Yalçıner, Hakan (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: Deterioration due to corrosion becomes a more serious problem when the exact time of expected earthquakes is unknown. Therefore, the prediction of performance levels of corroded reinforced concrete (RC) structures is important to prevent serious premature damage. Many models have been developed regarding the effects of corrosion as a function of time. It is possible to evaluate and identify the performance level of RC structures as immediate occupancy (IO), life safety (LS), collapse prevention (CP), and collapse (C). The first part of this study contributes to an understanding of time dependent effects of corrosion on seismic performance levels of corroded RC buildings that will be a guideline for the further studies for strengthening and assessing of RC buildings. The developed model in the first part of this thesis provide to predict the time dependent seismic performance levels of RC buildings by considering three major effects of corrosion (e.g., deformation due to bond-slip relationships, loss of cross sectional area of reinforcement bars and reduction in concrete compressive strength). In second part of this thesis, the effect of corrosion on the bond strength between reinforcement bars and concrete was studied in a series of experiments. An accelerated corrosion method was used to corrode the reinforcement bars embedded in concrete specimens. Pullout tests were performed to develop an empirical model for the ultimate bond strength by evaluating bond strengths in two different concrete mixes, three concrete cover depths and different mass losses of reinforcement bars after corrosion. Bond-slip relationships for the different corrosion levels were compared for different concrete classes and concrete cover depths. In contrast to developed models found in the literature for the prediction of ultimate bond strength, the newly developed bond strength models in this study provide to predict the bond strength as a function of corrosion level, concrete strength level, crack width and cover-to-diameter (c/D) ratios. It was found that previously developed bond strength models do not represent the actual corrosion behaviour where the bond strength decreases rapidly with increasing corrosion level in those models. Keywords: Corrosion, time-history analysis, performance levels, pullout test, bond strength, bond-slip relationship. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Korozyondan dolayı meydana gelen kötüleşme ileride olması depremlerin kesin zamanın bilinmemesi ile daha çok ciddi bir problem haline gelir. Bundan dolayı korozyonlu betonarme yapıların performans seviyelerinin tahmin edilmesi erken hasarların önüne geçilmesi için önemlidir. Korozyonun zamana bağlı olarak etkileri hakkında birçok model geliştirilmiştir. Ayrıca betonarme yapıların performans seviyelerini hemen kullanılabilir, can güvenliği, göçme öncesi ve göçme olarak değerlendirmek ve tanımlamak mümkündür. Bu çalışmanın ilk bölümü zamana bağlı korozyon etkilerinin korozyonlu betonarme binalar üzerindeki sismik performans seviyelerin anlaşılmasına katkıda bulunmaktadır ki ileriki çalışmalara betonarme yapılarının güçlendirilmesi ve değerlendirilmesi için bir rehber olacaktır. Bu tezin birinci bölmünde geliştirilen model, korozyonun başlıca üç etkisini (örneğin, aderans-kayma ilişkisinden dolayı deformansyon, donatı alanındaki kayıp ve beton basınç mukavvemetindeki azalma) dikkate alarak betonarme yapıların zamana baglı olarak performans seviyelerini tahmin etmeyi sağlamaktadır. Bu tezin ikinci bölmümde ise korozyonun donatı ve beton arasındaki aderans kuvveti üzerindeki etkisi bir takım seri deneyler ile çalışılmıştır. Beton numuneleri içerisine yerleştirilen donatılar hızlandırılmış korozyon metodu ile paslandırılmıştır. Aderans kuvvetini iki farklı beton karışımı, üç farklı paspayı ve farklı korozyon kütle kayıplarında değerlendirerek deneysel bir nihai aderans kuvvet modeli geliştirmek için çekme deneyi yapılmıştır. Farklı korozyon oranlarındakı aderans-kayma ilişkisi farklı beton sınıfları ve beton paspayları için karşılaştırılmıştır. Nihai aderans kuvvetini tahmin etmek için literatürde bulunan modellerden farklı olarak, bu tezin ikinci bölümünde yeni geliştirilen aderans modeli, aderans kuvvetini korozyon oranı, beton mukavvemeti, çatlak genişliği ve paspayı donatı oranına bağlı bir fonksiyon olarak tahmin etmeyi sağlamaktadır. Daha önce geliştirilen aderans modellerinin gerçek korozyon davranışını sergilemediği bulunmuştur ki bu modellerde aderans kuvveti artan korozyon oranıyla ani azalım göstermektedir. Anahtar Kelimeler: Korozyon, zaman-tanım analizi, performans seviyeleri, çekme deneyi, aderans kuvveti, aderans-kayma ilişkisi.
Doctor of Philosophy in Civil Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2012. Supervisor: Assoc. Prof. Dr. Özgür Eren.
Keywords: Civil Engineering; Buildings, Reinforced Concrete; Corrosion - Time-History Analysis - Performance Levels; Pullout Test - Bond Strength - Bond-Slip Relationship